GREEN TOURISM COMMUNICATION POLICY: THE MINISTRY OF TOURISM AND CREATIVE ECONOMY'S SUSTAINABLE PRACTICES IN BUILDING DIGITAL ECOTOURISM AWARENESS - Wira Yoga Pangestu; Anang Anas Azhar (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to analyze the strategy and acceptance of the Ministry of Tourism and Creative Economy (Kemenparekraf)'s green tourism communication policy in building digital ecotourism awareness in Indonesia. Using a descriptive qualitative approach and a constructivist paradigm, this study combines data from policy documents, digital observations through Brand24, and in-depth interviews with policy actors, academics, and ecotourism practitioners. The results show that Kemenparekraf's digital communication strategy through campaigns such as #TravelResponsibly, Green Parekraf, and Green Tourism Training has successfully transformed government communication patterns to be more participatory and interactive. Public acceptance of this policy tends to be positive, where the public is not only a recipient of messages, but also participates in producing content and creatively articulating the meaning of sustainability in the digital space. These findings are examined through the perspectives of Innovation Diffusion Theory and the Sustainable Communication Model, which emphasize the importance of two-way communication in the adoption of sustainability values. This research contributes to strengthening the discourse on digital environmental communication by positioning green tourism as a collaborative social movement that builds eco-conscious digital citizenship in Indonesia.